Differentiation of grain orientation with corrosive and colour etching on a granular bainitic steel. (August 2017) - Reisinger, S.; Ressel, G.; Eck, S.; Marsoner, S.
Highlights: It is possible to identify the {100} crystal orientation in the investigated steel, by means of Nital and Klemm etching. A cross section after Klemm etching showed, that bainite is also removed during colour etching and there is no removal on retained austenite. The cross section also showed that on a {100} crystal orientation the deposit thickness is approximately 39 nm and on a {110}/{111} crystal orientation 29 nm. The luminescence, which is directly affected by the deposit thickness, is around 100 for a {100} crystal orientation and approximately 120–150 for a {110}/{111} crystal orientation. It can be confirmed that Klemm etching also allows the determination of the retained austenite content via an area counting, which agrees well with XRD measurements. Abstract: This study presents a detailed verification of the etching methods with Nital and Klemm on a granular bainitic steel. It is shown that both methods allow the identification of the crystal orientation, whereas Klemm etching enables also a quantification of the apparent phases, as also retained austenite can be distinguished from the other bainitic microstructures. A combination of atom probe tomography with electron-back-scattered-diffraction showed that both etching methods emphasize the bainitic {100} crystal orientation. However, a cross-section produced by focused ion beam evidenced that Klemm etching leads to the formation of a topography of the different oriented bainitic crystals that directly affects the thickness and therefore the apparent colour of the deposited layer formed during etching.